Addressing non-tariff measures to promote Pakistan's textile sector - Rabia Manzoor; Vaqar Ahmed; Asif Javed (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2020)
The paper aims to identify the various types of non-tariff measures (NTMs) affecting Pakistan's textile sector. The textile industry is of great importance to Pakistan and is a major contributor to its gross domestic product. However, Pakistan's textile exports are facing market access challenges, in part due to trade barriers of some developed countries. An in-depth analysis of Pakistan's textile sector and NTMs country-wise and category-wise for the period of 2010-2017 was conducted. Statistics about the textile industry of Pakistan were obtained from the State Bank of Pakistan, while categorical export data on NTMs was taken from UNCTAD's TRAINS database. Face-to-face informal interviews were also conducted with 15 participants from relevant stakeholder groups, including public and private sector officials. The authors found that Pakistan's global share in textiles has declined significantly since 2010 and that it relies heavily on a few international markets such as the United States, China and the European Union. Turkey was found to have the highest number of NTMs targeting textile products, followed by the United States. Additionally, not only do countries importing Pakistani goods impose NTMs, Pakistan's own export procedures also hamper the trade. Interviewed exporters mentioned that they face difficulties in the costly and time-consuming acquisition of certification, whereas Government officials claimed the certification process improved competitiveness. Exporters also complained about the high cost of doing business, which results in the shifting of exports to China, Bangladesh and India. The paper recommends that trade agreements and their implementation be rationalized and simplified, uniform certification requirements for exporters be implemented to save costs and time, cheaper tests be made available in Pakistan rather than abroad, and that business-to-business forums be developed to promote information exchange. It is also suggested that a clear framework to deal with NTMs is needed. The development of Pakistan's textile exports will be difficult to sustain without addressing these challenges.
Keywords: F1; F13; O24; 330; Textile industry; export performance; non-tariff measures; Pakistan